Meeting the physical activity guidelines and survival after breast cancer: findings from the after breast cancer pooling project - Beasley, Jeannette M.; Kwan, Marilyn L.; Chen, Wendy Y.; Weltzien, Erin K.; Kroenke, Candyce H.; Lu, Wei; Nechuta, Sarah J.; Cadmus-Bertram, Lisa; Patterson, Ruth E.; Sternfeld, Barbara; Shu, Xiao-Ou; Pierce, John P.; et al. (Breast cancer research and treatment, 2012)
The 2008 Physical Activity (PA) Guidelines recommend engaging in at least 2.5 h (10 MET-hours/week) of moderate intensity PA per week (defined as 4 METs) to reduce risk of morbidity and mortality. This analysis was conducted to investigate whether this recommendation can be extended to breast cancer survivors. Data from four studies of breast cancer survivors measuring recreational PA from semi-quantitative questionnaires a median of 23 months post-diagnosis (interquartile range 18–32 months) were pooled in the After Breast Cancer Pooling Project ( n = 13,302). Delayed entry Cox proportional hazards models were applied in data analysis with adjustment for age, post-diagnosis body mass index, race/ethnicity, menopausal status, TNM stage, cancer treatment, and smoking history. Engaging in at least 10 MET-hours/week of PA was associated with a 27% reduction in all-cause mortality ( n = 1,468 events, Hazard Ratio (HR) = 0.73, 95% CI, 0.66–0.82) and a 25% reduction in breast cancer mortality ( n = 971 events, HR = 0.75, 95% CI 0.65–0.85) compared with women who did not meet the PA Guidelines (<10 MET-hours/week). Risk of breast cancer recurrence ( n = 1,421 events) was not associated with meeting the PA Guidelines (HR = 0.96, 95% CI, 0.86–1.06). These data suggest that adhering to the PA guidelines may be an important intervention target for reducing mortality among breast cancer survivors.